Knowledge and culture: two significant issues for local level development programme analysis - Vasconcellos, Ana Maria de Albuquerque; Vasconcellos Sobrinho, Mário (Interações, 2015)
The paper aims to propose a theoretical framework to analyse development programmes acting at local level. Particularly, the paper stresses two key concepts that should be taken into account in the process of implementing development programme at local level, namely knowledge and culture. The paper shows that understanding of knowledge as a social construction contrasts with the rational, positivist view of knowledge derived exclusively from a scientific viewpoint. The paper explains if development relates to increasing or improving people living standards through social and economic changes, then it will impact on, and be mediated through knowledge and culture.